Is Developmental Change in Gender-Typed Behavior Associated with Adult Sexual Orientation? - Kahn, Nicole F. (Dev Psychol, 2018)
The goal of this paper was to examine gender-typed behavior longitudinally and to consider its relationship with sexual orientation in adulthood. Data were from 10,624 respondents who completed Waves 1 (adolescence), 3 (emerging adulthood), and 4 (early adulthood) of the National Longitudinal Study of Adolescent to Adult Health (Add Health). First, we described the distributions of gender-typed behavior by adult sexual orientation at each of the three developmental stages. Next, we performed multilevel mixed regression models to assess longitudinal variation in gender-typed behavior from adolescence to adulthood within sexual orientation groups. Results showed that gender-typed behavior varied both within and between sexual orientation groups, as well as over time. For males, the differences in gender-typed behavior among the sexual orientation groups were relatively consistent at each stage, while differences in gender-typed behavior among sexual orientation groups varied more at each stage among females. Longitudinal models exhibited curvilinear patterns, such that gender-typed behavior strengthened from adolescence to early adulthood but peaked in emerging adulthood. To our knowledge, this is the first study to use population representative data to study gender-typed behavior both prospectively and at multiple time points from adolescence to adulthood, and to consider how such behavior is related to adult sexual orientation. This research contributes to a growing body of prospective literature on the link between gendered behavior and sexual orientation and provides further justification for more age- and cohort-specific measures of gender-typed behavior in future research.